Implementasi Wearable Device Untuk Klasifikasi Postur Keadaan Tubuh Berbasis Data Sensor MPU6050 Menggunakan Metode Naive Bayes - Vira Muda Tantriburhan Mubarak; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Body posture condition is a body condition or body position of someone when do several kind of activities, for example sit, stand, walk, etc. Marking toward posture is very important in health aspect. Except for health, a body condition can be used in various things too, one of the example is in loT (Internet of Things), when body condition can controls electronic devices in house. Because of that, it needs a study of a system to clarify a body posture condition. In this study, the system is made in wearable device form, where the system can be paired to someone's body easily. Parameter which used for detect the body posture condition is a angle and acceleration in some body points that are chest, right thigh, and left tight. The parameter value be obtained from reading three sensors MPU6050 and be processed with Naive Bayes method in Raspberry Pi Zero W microcontroller. Naive Bayes is chosen as a method to clarify because Naive Bayes is a clarify method which has high accuracy and has fast computation performance. The system also can send the result to android application through Bluetooth protocol and the result can be shown in the application. From the result of system trial can be known error presentation of sensor reading MPU6050 is 1,392%. After that, the researcher also do trial system of Naive Bayes accuracy with 55 practice data and 28 trial data, from the trial, it found 100% accuracy with time computation during 4,178 ms (miliseconds).